Socket-shield technique with minimally invasive osteotomy preparation as well as simultaneous sinus lift utilizing Densah Bur and platelet-rich fibrin membrane followed by immediate implant placement in a symptomatic posterior endodontically treated decayed root stumps site: A case report with 1-year follow-up - Rahul Deshwal; Sanjeev Kumar Salaria; Ritu Dahiya; Neha Deshwal (Journal of Indian Society of Periodontology, 2022)
Soft-tissue defect and alveolar bundle bone resorption (horizontally and vertically) are inevitable events following tooth extraction predominately on the buccal aspect which will impact the implant surgical planning starting from implant size selection, position, emergence profile, etc. To overcome the same, complex soft and hard tissue regeneration procedures have been recommended in the literature but they are highly expensive and technique sensitive too. To prevent buccal bone resorption and gain good emergence profile socket-shield technique (SST) is widely recommended. Additionally, in order to improve implant biomechanical primary stability, bone mineral density, and bone to implant contact novel osseodensification approach is recommended for osteotomy preparation and sinus membrane lift whereas platelet rich fibrin (PRF) autograft is a suitable alternative for the protection of Schneiderian membrane during immediate implant placement in sinus sub cavity. The present case report describes the successful single-stage management of symptomatic endodontically maltreated posterior root stumps site utilizing SST in conjunction with Densah Bur and PRF autograft-assisted minimally invasive osteotomy preparation and sinus lift with immediate implant placement.